Physical and sensory properties of oat cakes - Han, Liqing; Huff, Harold E; Hsieh, Fu-hung (MTT, 2004)
Oat-based product has long been identified as a highly desirable food. It has a high nutritional profile due to its high concentration of protein, good distribution of amino acids, and rich fiber content when compared to other grains. Puffed oat cakes may appeal to consumers due, in part, to their low fat, low calorie, high fiber, and whole grain properties which fit well with healthy claims, key snacking trends, and the shift in American dietary attitudes. However, their physical and sensory properties have not been reported in the literature. Oat cakes were produced by a two-step process: 1) extrude oat flour to make pellets and 2) puff oat pellets in a rice cake machine. A 2×3×4×3 factorial design consisting of four variables and with 2 replications was used to study the effects of extrusion, tempering and puffing conditions on the puffed oat cakes. The four independent variables are extrudate moisture content (30 and 34 % wb), tempering moisture content (10, 12, and 14 % wb), heating temperature (238, 243, 249, and 254 °C), and heating time (4, 6, and 8 s). Physical properties of oat cakes (specific volume, color, hardness, and integrity) and descriptive sensory analysis were conducted. The results showed that extruded oat pellets can be successfully puffed by a rice cake machine to make oat cakes. All the four processing variables (heating time, heating temperature, extrudate moisture content, and tempering moisture content) had significant effects on the oat cake s physical and sensory properties. Heating time had the most significant effect. Increasing heating time resulted in oat cakes with increased specific volume, integrity, and redness, but lower lightness and yellowness. Also, Pincipal Component Analysis (PCA) showed that high correlations existed between instrumental and sensory descriptive analysis.
Keywords: Ka; oat cake; physical properties; descriptive sensory analysis; puffing